Application of microscale combustion calorimeter to characterize protective properties of bovine leather - Žuvela Bošnjak, Franka (Array, 2020)
The quality and properties of fire resistance are crucial to the selection of leather for the production of protective fire fighting boots, which has a primarily protective role. During fire extinguishing it is exposed to extremely high and low temperatures, chemicals (acids and alkalis), mechanical loads, etc. The properties of fire resistance were tested on two samples of bovine leather (BL1, BL2). Burn resistance test has been carried out in accordance with the requirements of the technical standards for the burn resistance test: HRN EN ISO 15090: 2012, t, 7.3 - Firefighters and rescue services. The mentioned two samples were individually tested according to HRN EN ISO 15025: 2003. The test procedure was carried out by the "Flame Expansion Testing Method". Moreover, in this research used Microscale Combustion Calorimeter (MCC) Govmark, UK because that was designed for produce the maximum heating rate capability similarly the heating rates in fires and give as a lot of flammability parameters. The analysis of physicochemical properties of samples was performed using Fourier transform infrared (FTIR) spectroscopy. The surface morphology of the samples was studied using a Field Emission Scanning Electron Microscopy (FE-SEM). The measurement of the above samples on MCC was performed according to ASTM D7309. From the obtained HRR results, it is evident that BL1 sample has a better thermal stability than the BL2 sample.